Sistem Pengembangan Deteksi Kamera Berbasis Artificial Intelligence (AI) dalam Toko Ritel - Puji Astuti, Fitria Dewi; Nusantoro, Jawoto; Febri Darmayanti, Elmira (Universitas Muhammadiyah Metro, 2025)
This research was carried out with the aim of introducing an artificial intelligence-based camera detection system to increase the optimization of retail store inventory. By utilizing computer vision recognition technology to manage and increase inventory efficiency. In this research, the Yolo v5 model will be used. You Only Look Once (Yolo), while the type of data used is secondary data obtained from dataset collection sites, namely Kaggle and Roboflow. The results of this research create the latest solutions to help retail stores adapt to increasingly fierce competition and provide better service to customers. The research concludes that real-time stock monitoring provides store management with instant information about product availability, enabling quick decision making and more effective responses